Khem Bedi Singh Haveli at Kallar Sayedan Rawalpindi, Center of Socio Cultural and Religious Activities - Samina Saleem, Samina Saleem (Ancient Pakistan, 2016)
This research paper is a kind of a case study of a residential building almost 200 years old, which has not been documented. Such building complexes were not only used for residential purpose, but also for some kind of religious or social significance in Subcontinent. They are commonly known as Havelies, a Sanskrit word for a Residential palace like structure for the Elite of the area. It has been discussed in detail that these kinds of buildings (Havelies) commonly had other structures attached to the residence in the same boundary, like stables, guard rooms, worship areas and sometimes graveyards. This specific Haveli or Mansion is so rich and fascinating in its architectural style and art of Mural painting that it not only tells us about the religious stories from Hindu Epics, but also of Sikh Gurus and stories from the life of the Maharajas (kings) of India. The wood work in the building is also very intricate especially doors and windows are carved with floral and geometrical designs. The architectural style used in this Havelies is a combination of Hindu and Mughal building style. The technique used in Murals is Fresco. The general condition is deteriorating. The main objective to document this Haveli is to take the attention of the authorities for the restoration and preservation of such buildings, which are dying or vanishing with the passage of time and because of the negligence of the Archaeology Department and Ministry of Culture and Heritage. This building is commonly known as Bedi Mehal (Bedi Palace), which has been a place of social and religious gathering and was used as a center for the Sikh people of the area of Kaller Sayedan at the time of partition, when they moved to Indian side. And present condition of the building is pathetic, which needs attention of the tourists also.